The Dynamics of Land Tenure in Multi-ethnic Society - Bumulo, Sahrain; Adiwibowo, Soeryo; Sjaf, Sofyan (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2017)
ABSTRACTThis study aims to analyze the dynamics of land tenure in the multi-ethnic society. This research was conducted in District of Randangan,Pohuwato Regency. With a qualitative approach, this research involved 27 informants from various ethnic backgrounds (Gorontalo, Java, Bali, and Bugis) and profession (bureaucracy, NGO, and academic actors). The results of this study indicate that land tenure in the study sites has ethnic dimensions. This is evidenced by the existence of land tenure segregation, in which Bugis ethnic control of land in the coastal areas used for fishpond activities. Furthermore, ethnic Javanese controlled land in the hilly areas used as agricultural and plantation activities, while the ethnic Gorontalo (local), more widely spread in the sub-district government structure, and private. The existence of segregation of land tenure, trigger the emergence of turmoil in society by using ethnic identity as its domain. Therefore, the issue of locals versus migrants colored the polemic at the study site.Furthermore, the granting of access is also based on several actors’ interests, including socio-economic, political, and demographic interests.Keywords: Dynamics, land tenure, multiethnic societyABSTRAKPenelitian ini bertujuan untuk menganalisis dinamika penguasaan lahan dalam masyarakat multietnik. Penelitian ini dilaksanakan di Kecamatan Randangan Kabupaten Pohuwato. Dengan pendekatan kualitatif, penelitian ini melibatkan 27 informan dari berbagai latar belakang etnik (Gorontalo, Jawa, Bali. dan Bugis) dan profesi (birokrasi, LSM, dan akademisi). Hasil penelitian ini menunjukkan bahwa penguasaan lahan di lokasi studi memiliki dimensi etnisitas. Hal ini dibuktikan oleh adanya segregasi penguasaan lahan, di mana etnik Bugis menguasai lahan di wilayah “pesisir” yang digunakan untuk aktivitas tambak ikan. Selanjutnya, etnis Jawa menguasai lahan di wilayah “perbukitan” yang digunakan sebagai aktivitas pertanian dan perkebunan, sedangkan etnis Gorontalo (lokal), lebih banyak tersebar di struktur pemerintahan kecamatan, dan swasta. Adanya segregasi penguasaan lahan, memicu timbulnya gejolak di masyarakat dengan menggunakan identitas etnis sebagai domainnya. Oleh karena itu, isyu penduduk lokal versus pendatang mewarnai polemik di lokasi studi. Di sisi lain, proses penguasaan lahan di lokasi studi dilatar-belakangi oleh adanya keterlibatan berbagai aktor (berbasis etnis) dalam pemberian akses kepada anggota etnisnya masing-masing. Selanjutnya, pemberian akses juga didasarkan pada beberapa kepentingan aktor, di antaranya adalah kepentingan sosial-ekonomi, politik, dan demografi.Kata Kunci: dinamika, penguasaan, lahan, masyarakat multietnik